2016
DOI: 10.1038/jhg.2016.79
|View full text |Cite
|
Sign up to set email alerts
|

Target resequencing of neuromuscular disease-related genes using next-generation sequencing for patients with undiagnosed early-onset neuromuscular disorders

Abstract: Neuromuscular disorders are clinically and genetically heterogeneous diseases with broadly overlapping clinical features. Progress in molecular genetics has led to the identification of numerous causative genes for neuromuscular disorders, but Sanger sequencing-based diagnosis remains labor-intensive and expensive because the genes are large, the genotypes and phenotypes of neuromuscular disorders overlap and multiple genes related to a single phenotype exist. Recently, the advent of next-generation sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
1
18
1
Order By: Relevance
“…[26][27][28] In our study, we report an overall diagnostic yield of 15.1% (22.4% in children and 13.7% in adults) in a large cohort of patients with suspected muscle disorders from outpatient clinics across Canada. Although this is lower than most previous studies, [2][3][4][5][6][7] the present estimation is more likely to be representative of current clinical practice, as it relies on less restrictive criteria for testing (such as previous abnormal muscle biopsy or limb-girdle weakness pattern), does not focus on suspicion of a specific group of disorders (e.g., LGMDs), and involves a large number of different physicians (187) from the common medical specialties involved in the care of patients with suspected muscle disorders: neuromuscular specialists, general neurologists, and geneticists. As expected, the majority of patients (61.7%) were seen by a neuromuscular specialist.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…[26][27][28] In our study, we report an overall diagnostic yield of 15.1% (22.4% in children and 13.7% in adults) in a large cohort of patients with suspected muscle disorders from outpatient clinics across Canada. Although this is lower than most previous studies, [2][3][4][5][6][7] the present estimation is more likely to be representative of current clinical practice, as it relies on less restrictive criteria for testing (such as previous abnormal muscle biopsy or limb-girdle weakness pattern), does not focus on suspicion of a specific group of disorders (e.g., LGMDs), and involves a large number of different physicians (187) from the common medical specialties involved in the care of patients with suspected muscle disorders: neuromuscular specialists, general neurologists, and geneticists. As expected, the majority of patients (61.7%) were seen by a neuromuscular specialist.…”
Section: Discussioncontrasting
confidence: 68%
“…1 Therefore, genetic testing is increasingly used and can be obtained in a noninvasive manner. Across different countries such as Canada, the United States, China, Korea, Germany, the United Kingdom, Egypt, Poland, Australia, and Japan, gene panel sequencing has a yield varying from 16% to 65%, [2][3][4][5][6][7] depending on subgroups of patients' selection, whereas exome sequencing has a yield in between 13% and 69% [8][9][10][11][12][13][14][15] in different settings. Its superiority over gene panel, in diagnosing common etiologies, remains to be quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used a gene panel, rather than WES or genome sequencing, approach for diagnosis in neuromuscular disease [ 15 23 ], and whether this is best practice in diagnostics is a topic for debate [ 13 ]. Although gene panels may be more cost effective in terms of cost per gene sequenced than individual genetic tests, and also have the advantage of greater depth of coverage in comparison to WES, they are still phenotype-driven testing and as such require the correct panel of genes to be selected [ 13 , 38 ] which may limit the rate of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Next generation sequencing techniques (NGS) provide a potential way to overcome diagnostic delays due to genetic heterogeneity and also the possibility to identify novel genetic causes of muscle disorders [ 13 , 14 ]. Several studies have reported on the application of gene panels [ 15 23 ] or WES [ 24 , 25 ] for the diagnosis in undiagnosed muscle disease, achieving diagnostic rates from 16 to 76%, with the highest diagnostic rate achieved in patients with no prior genetic testing [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…With growing acceptance and availability of genetic analysis and its dramatic technical progress, many parents and clinicians now decide for gene tests as first line diagnostics. The massive parallel sequencing technic offers a quick and cost-effective strategy to reach a diagnosis in approximately 40 to 50% of patients (compare also 5,8 ). Even with a relatively small gene panel as presented here, in each patient a list of variants has to be evaluated.…”
Section: Discussionmentioning
confidence: 99%